SYNTHESIS OF TRADITION AND MODERNITY - Chackalackal, Saju (Journal of Dharma, 1988)
Man has the noble faculty of memory to remember his past and to make use of it in the present with necessary changes "in the light of the signs of the times." The aim of the present study is to explore and unveil the attempts made by S. Radhakrishnan towards a reconciliation or a creative synthesis of tradition and modernity, which is a perennial problem ever since the dawn of human civilization. It was his belief that "nothing is good simply because it is ancient. and no composition is faulty merely because it is anew."